PacBio sequencing revealed variation in the microbiota diversity, species richness and composition between milk collected from healthy and mastitis cows. Issue 7 (22nd July 2021) - Ma, Teng; Shen, Lingling; Wen, Qiannan; Lv, Ruirui; Hou, Qiangchuan; Kwok, Lai Yu; Sun, Zhihong; Zhang, Heping
Abstract : Mastitis is the economically most important disease of dairy cows. This study used PacBio single-molecule real-time sequencing technology to sequence the full-length 16S rRNAs from 27 milk samples (18 from mastitis and nine from healthy cows; the cows were at different stages of lactation). We observed that healthy or late stage milk microbiota had significantly higher microbial diversity and richness. The community composition of the microbiota of different groups also varied greatly. The healthy cow milk microbiota was predominantly comprised of Lactococcus lactis, Acinetobacter johnsonii, and Bacteroides dorei, while the milk from mastitis cows was predominantly comprised of Bacillus cereus . The prevalence of L. lactis and B. cereus in the milk samples was confirmed by digital droplets PCR. Differences in the milk microbiota diversity and composition could suggest an important role for some these microbes in protecting the host from mastitis while others associated with mastitis. The results of our research serve as useful references for designing strategies to prevent and treat mastitis.